Isolation and identification of flower yeasts for the development of mixed culture to produce single-cell protein from waste milk. (June 2020) - Myint, Khin Thandar; Otsuka, Mitsuo; Okubo, Airi; Mitsuhashi, Ryoko; Oguro, Asami; Maeda, Hironori; Shigeno, Toshiya; Sato, Kiyoshi; Nakajima-Kambe, Toshiaki
Abstract: On the need to utilize waste milk, local flower yeasts in Tsukuba, Japan, were isolated, identified, and tested for single-cell protein (SCP) production using waste milk without additives. This study aimed to identify an efficient yeast consortium for SCP production. Growth, assimilation ability, bioactive compound synthesis, and waste milk treatment efficiency of 53 isolates were screened. From the isolates, Kluyveromyces lactis (TY-98) and Rhodotorula graminis (TY-99) were selected. The effects of different incubation temperatures, initial pH, and inoculum size ratio on SCP production, in monoculture, mixed culture, and sequential culture were studied. Total organic carbon (TOC) reduction of waste milk by the mixed culture (88%) was higher than that of TY-99 monoculture (33%), TY-98 monoculture (73%), and sequential culture (67%). Mixed culture under optimized conditions produced high SCP amounts (43.8 DCW g/L) and carotenoids (1.8 mg/L). This study provided a potential approach to vitamin-enriched feed production and waste milk treatment. Highlights: K. lactis and R. graminis as a consortium for SCP production from waste milk Optimum culture conditions were 30 °C, initial pH 6, and 1:10 inoculum ratio. Mixed culture improved carotenoid-rich SCP productivity and TOC removal.